2021
DOI: 10.1097/naq.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Using Text Messages to Support Nurse Well-being

Abstract: The COVID-19 pandemic caused significant nurse stress and contributed to burnout for a number of reasons, including but not limited to personal protective equipment shortages, furloughs, overtime, reassignment to unfamiliar work environments, and alternate staffing patterns, all of which contribute to grief, loss, fear, and anger. While the nursing profession and employers offered support and psychological first-aid resources, there was a disconnect in effectively linking stressed nurses with these needed reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Therefore, it is important to pay attention to the well-being of all nurses, including leaders, particularly as we view the lingering results of the pandemic on key workforce outcomes. Several publications describe interventional studies that may improve nurse well-being such as education/ self-reflection (Sawyer et al, 2022), resilience retreats (Cunningham & Çayir, 2021), text messaging (Kelly et al 2021), wellness partners (Teall & Melnyk, 2021) and transcendental meditation (Azizoddin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to pay attention to the well-being of all nurses, including leaders, particularly as we view the lingering results of the pandemic on key workforce outcomes. Several publications describe interventional studies that may improve nurse well-being such as education/ self-reflection (Sawyer et al, 2022), resilience retreats (Cunningham & Çayir, 2021), text messaging (Kelly et al 2021), wellness partners (Teall & Melnyk, 2021) and transcendental meditation (Azizoddin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The use of mobile technology through short text messages can be considered an effective option for encouraging nurses and supporting their well-being. Kelly et al (2021) found that the satisfaction rate of nurses who were on the “RNconnect 2 Wellbeing” application ranged from 73 % to 86 % and that 48 % of them integrated the resources offered through the messages on this application into their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mobile technology through short text messages can be considered an effective option for encouraging nurses and supporting their well-being. Kelly et al (2021) found that the satisfaction rate of nurses who were on the "RNconnect 2…”
Section: Discussionmentioning
confidence: 99%
“…7 While TM is increasingly used for general communication between healthcare personnel, its use as a supportive intervention is not well known. 8 This article evaluates the benefits of TM in providing simple, constant, and effective support, specifically in the nursing population. 8,14 Without adequate support to cope with these circumstances, nurses' well-being declines, leading to increasing absenteeism and reduced ability to problemsolve, which have negative effects on patient outcomes.…”
Section: Shutterstock/peopleimagescom -Yuri Amentioning
confidence: 99%
“…8 This article evaluates the benefits of TM in providing simple, constant, and effective support, specifically in the nursing population. 8,14 Without adequate support to cope with these circumstances, nurses' well-being declines, leading to increasing absenteeism and reduced ability to problemsolve, which have negative effects on patient outcomes. 12,15 Not only clinical RNs but also APRNs have reported significant levels of stress and less resilience.…”
Section: Shutterstock/peopleimagescom -Yuri Amentioning
confidence: 99%